Realization and Application of Information Expansion on Water Conservancy and Hydropower Engineering Based on IFC Standard - FU Zhihao; LYU Bin; YANG Chuhua; WANG Cunhui (Renmin Zhujiang)
The application of BIM technology in the entire life cycle of water conservancy and hydropower engineering has attracted more and more attention,and the importance of project information based on BIM model as key production factors has become increasingly prominent.Currently,the storage standard of water conservancy and hydropower engineering information model usually adopts the information expansion based on the IFC standard.In practical applications,there are some problems such as insufficient information and non-implementation of standard in the design software.To further carry out research and application based on model information,it is necessary to realize the dynamic expansion to model information and integrate it in design software for ease of use.Based on the industry foundation class standard (IFC),this paper discusses the method of information expansion under the IFC standard system,and sorts out the realization method of IFC standard expansion on the basis of Microstation by C# language.The information processing program developed based on Microstation can easily and quickly add,view,update,and expand the information required by the project as needed.The standard stored in the XML file format,which is more convenient for future research and sharing.The program has been applied and verified in actual projects,and the delivery of the three-dimensional information model has been successfully completed.The Microstation-based IFC information expansion method is simple and feasible,with strong portability,which can lay a good foundation for subsequent research on data delivery standards,project model information expansion,and project data analysis,and provide references for similar projects.